Vulnerability Assessment and Spatio-Temporal Difference Analysis of Inland Fisheries Flood Disaster in China - Lu, Honggang; Zheng, Jiaxi; Ou, Hanyun; Liu, Yinong; Li, Xijian (Frontiers in Ecology and Evolution, 2022)
Vulnerability research is an active option for fisheries to adapt to climate change. Based on the vulnerability analysis framework of the vulnerability scoping diagram, a vulnerability evaluation index system for inland fisheries in China was constructed in three dimensions, including exposure, sensitivity and adaptive capacity. The entropy method was used to evaluate the flood disaster vulnerability of China's inland fisheries from 2010 to 2019 and its decomposition. The temporal and spatial differences between vulnerability and its decomposition were analyzed. kernel density estimation and factor contribution model were used to analyze the changing trend of vulnerability and main influencing factors. The results show that: during the study period, the vulnerability of inland fisheries in China to flood disasters showed a fluctuating downward trend, and the high vulnerability areas were mainly distributed in South China and the middle and lower reaches of the Yangtze River; the exposure index first decreased and then increased, and the high-exposure regions were mainly concentrated in the middle and lower reaches of the Yangtze River; the sensitivity index first decreased and then increased, and the high-sensitivity areas were concentrated in North-east China, the middle and lower reaches of the Yangtze River, and South China; the adaptive capacity index showed a downward trend, and the areas with lower adaptive capacity were concentrated in the South-west and North-west. From the factor contribution model, the economic losses of fishery floods and the affected area had the greatest impact on the exposure index; fingerling production and freshwater fishery production had the greatest impact on the sensitivity index; the index with a lower contribution to the adaptive capacity index was the total power of fishery machinery and fishery technology promotion. Therefore, building reservoirs, optimizing aquaculture layout and promoting fishery modernization are the keys to reducing the vulnerability of inland fisheries to flood disasters.